KAJI TINDAK PENGENDALIAN HAMA PENGGEREK BUAH KAKAO (Conopomorpha cramerella Snellen) DENGAN PESTISIDA NABATI - Nuriadi, Nuriadi; Gusnawaty, HS (Jurnal Agroteknos, 2013)
This research aimed to know the effectivity of botanical pesticide in retarding cocoa pod borer. The study was conducted using completely randomized design, with 7 treatments and 3 replications. Total number of trial units was 21. The results of the study showed that the ingredient botanical pesticide that gave significant effect was ingredients III with interval 5 days/application which can limit attack of pod from 100 % to 24,78 % and intencity attack from 92,56 % to 11,25 %. Keywords : botanical pesticide, cocoa pod borer, intencity attack